(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In the present modern society, where electricity is necessary for the lightening of homes and public buildings, the major problem in our localities is power wastes. To some extent electrical appliances such as lighting systems were left ON even in the absence of people in both private and public places. This is because traditional manual switching system is still employed in almost every building where one has to switch the room lights ON or OFF. Thus, a large amount of energy is being wasted if lights are left ON in the absence of people in those places. This work presents an intelligent energy saving system that can automatically power ON/OFF our lightening systems. The heart of this project is Passive Infrared (PIR) motion detector that can detects the radiated heat of a person and converts it to electrical signals, which is sent to switching circuit for processing. A low-cost fully automated energy saving system was designed and tested in physics laboratory of Umaru Musa Yar’adua University, Katsina, Nigeria. The system was able to detect movement of objects/humans within range of 6 meters in the lab to switch ON the light and also switch it OFF in their absence. Therefore, the designed system if explored will have the potentials of reducing energy waste and at the same time reducing one’s energy bills.